2013
DOI: 10.1093/ntr/ntt214
|View full text |Cite
|
Sign up to set email alerts
|

Prequit fMRI Responses to Pleasant Cues and Cigarette-Related Cues Predict Smoking Cessation Outcome

Abstract: Smokers with blunted brain responses to pleasant stimuli, relative to cigarette-related stimuli, had more difficulty quitting smoking. For these individuals, the lack of alternative forms of reinforcement when nicotine deprived might be an important factor underlying relapse. Normalizing these pathological neuroadaptations may help them achieve abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 55 publications
3
74
3
Order By: Relevance
“…Prior studies reported associations between increased attention bias toward drug-related cues and susceptibility to relapse. 11,12,[29][30][31][32][33] That relapse status did not have a significant impact on our results is not surprising because in the present study all individuals with CUD showed a significant reduction of drug use (in both abstinent and relapsed subgroups); however, additional longitudinal studies with longer follow-up are required.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…Prior studies reported associations between increased attention bias toward drug-related cues and susceptibility to relapse. 11,12,[29][30][31][32][33] That relapse status did not have a significant impact on our results is not surprising because in the present study all individuals with CUD showed a significant reduction of drug use (in both abstinent and relapsed subgroups); however, additional longitudinal studies with longer follow-up are required.…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, prospective neuroimaging studies modelling relapse vulnerability and future drug use have shown that reduced attention toward drug-related cues 11,12,[28][29][30] and increased attention toward non-drug-related reinforcers [31][32][33] predicted longer abstinence durations in individuals with substance use disorders. Although these studies are highly informative, many have been limited to the cross-sectional Background: Increased attention bias toward drug-related cues over non-drug-related intrinsically pleasant reinforcers is a hallmark of drug addiction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuroimaging studies of human smokers have consistently demonstrated heightened blood oxygenation level dependent (BOLD) response to smoking stimuli relative to neutral stimuli in the striatum and other interconnected brain regions (Buhler et al, 2010;David et al, 2005;Engelmann et al, 2012;McClernon et al, 2009;Sweitzer et al, 2013). Furthermore, alterations in striatal processing of smoking and other rewarding stimuli have been associated with increased craving (Sweitzer et al, 2013) and predict smoking behavior (Versace et al, 2014;Wilson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%